2018
DOI: 10.1186/s40538-018-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate variability on insect pests of cabbage: adapting alternative planting dates and cropping pattern as control measures

Abstract: Background: Considering the potential impact of climate change on the ecology of insect pests, different planting dates and cropping patterns were investigated as farm-level adaption to control insect pests of cabbage and improve productivity. Methods: This is a 3 × 4 factorial experiment setup in randomized complete block design including three planting dates (early, normal and late) and four cropping patterns (control-sole cabbage or tomato, tomato intercrop, Piper emulsion and insecticide) with four replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
(44 reference statements)
4
4
0
Order By: Relevance
“…Similarly, in 2020 wet season, the mean maximum and minimum temperatures of Boro experimental site (2013) who reported that cabbage insect pests are affected either positively or negatively with variations in seasons due to variations in rain precipitations and temperatures.In addition, P. xylostella larvae were significantly higher at Boro experimental site relative to Tengeru experimental site and varied significantly from season to season. These results agree withPatra et al (2013) andTanyi et al (2018) who reported that, the incidence and infestations of P. xylostella on cabbage crops vary from region to region. The rainfall precipitations and temperatures of Boro experimental site might have contributed the higher abundances of P.xylostella larvae compared with Tengeru study site whereas the abundance was low.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, in 2020 wet season, the mean maximum and minimum temperatures of Boro experimental site (2013) who reported that cabbage insect pests are affected either positively or negatively with variations in seasons due to variations in rain precipitations and temperatures.In addition, P. xylostella larvae were significantly higher at Boro experimental site relative to Tengeru experimental site and varied significantly from season to season. These results agree withPatra et al (2013) andTanyi et al (2018) who reported that, the incidence and infestations of P. xylostella on cabbage crops vary from region to region. The rainfall precipitations and temperatures of Boro experimental site might have contributed the higher abundances of P.xylostella larvae compared with Tengeru study site whereas the abundance was low.…”
supporting
confidence: 93%
“…The rainfall precipitations and temperatures of Boro experimental site might have contributed the higher abundances of P.xylostella larvae compared with Tengeru study site whereas the abundance was low. The results concur withTanyi et al (2018) andPatra et al (2013) who reported that, population building up of P. xylostella is favoured by warm conditions and rain precipitations of the region and the season. Moreover,Ayalew (2006) reported that rain precipitations and temperatures ranging from 25 to 33 °C have significant influences on the population of P. xylostella.…”
supporting
confidence: 92%
“…Multiplication of pests preferred the hot climatic condition (off-season) but in cold condition (Nov-Feb) very few insects infest the cabbage 26 . According to Tanyi 27 late plantation of cabbage (April) reduce the pest population of cabbage looper larvae, webworm larvae and P. xylostella when compared to normal and early plantings. This method is considered a feasible, cost-effective pest management strategy that can be implemented by the farmers.…”
Section: Current Biological Control Of Crucifer Pestsmentioning
confidence: 99%
“…The interaction of planting dates and Piper emulsion or intercropping treatments can be effectively used to control cabbage pests (diamondback moth, Plutella xylostella and cabbage webworm, Hellula undalis and cabbage Looper, Trichoplusini) to improve yields, with the late planting date as viable alternative farm-level adaptation to climate variability. These represent costeffective and environmentally friendly pest management strategies that can be adopted by farmers to control cabbage pests below the economic injury threshold and improve yield (Tanyi et al 2018). Similarly, insects employ pheromones and allelochemicals to perceive their surroundings, which is a crucial process.…”
Section: Integrated Pest Management (Ipm) and Recent Tools For Pest M...mentioning
confidence: 99%